Two new species of coastal Atyphella Olliff (Lampyridae: Luciolinae) - Saxton, Natalie A.; Powell, Gareth S.; Martin, Gavin J.; Bybee, Seth M. (Zootaxa, 2020)
Additional work on the islands of Vanuatu has improved our understanding of the actual diversity of South Pacific coastal fireflies. Prior to recent fieldwork in Vanuatu, the only known lampyrid from Vanuatu was Atyphella aphrogeneia (Ballantyne), a coastal species also found in Papua New Guinea. After further examination, we determined that specimens from Vanuatu formerly classified as Atyphella aphrogeneia actually belong to an undescribed species. New species, Atyphella maritimus Saxton and Powell and Atyphella marigenous Saxton and Bybee, are described from specimens collected in Vanuatu. An updated key for coastal Atyphella in the South Pacific is provided.